Ordering Africa : anthropology, European imperialism and the politics of knowledge - Tilley, Helen, 1968-; Gordon, Robert J., 1947- (Studies in imperialism (Manchester, England), 2017)
Provides the first comparative overview of the role of anthropology in colonial Africa. With essays exploring metropolitan research institutes, Africans as ethnographers and the transnational features of knowledge production, this volume both consolidates and extends a range of new research questions focusing on the politics of imperial knowledge.